Synovial Sarcoma in Head and Neck: A Case Report - Fonseca, Adriano Santana; Azevedo, Amanda Canário Andrade; Magalhães, Fabíola Moreira; Andrade, Nilvano Alves de (International Archives of Otorhinolaryngology, 2014)
Introduction Synovial sarcoma is a malignant tumor of mesenchymal pluripotent cells.Objectives We present a case of synovial sarcoma in the posterolateral wall of the oropharynx.Resumed report The patient, a 23-year-old woman, was admitted with a history of dysphagia and difficulty in breathing for 8 months, resulting in progressive deterioration and onset of snoring, muffled voice, and local pain. An oropharyngeal tumor in the left posterolateral wall touched the base of the ipsilateral tongue. The patient underwent endoscopic pharyngectomy to remove the lesion. Pathologic examination revealed synovial sarcoma with positive margins, and Mohs technique was proposed for margin control. The margins were disease-free, without the need for total laryngectomy. The pharynx was reconstructed with a microvascular forearm flap. The patient developed postoperative stability.Conclusion Despite its name, synovial sarcoma is rarely sourced directly from synovial membranes. It is most commonly found in the vicinity of large joints. The location at the head and neck, a location poor in synovial tissue, is unusual. Synovial sarcoma in the head and neck has an aggressive nature and poor prognosis. Resection with negative margins remains the foundation of therapy, which is not so easily achieved in the head and neck. It is important for the otorhinolaryngologist and head and neck surgeon to be familiar with this aggressive tumor, which carries high mortality and morbidity. The appropriate diagnosis and treatment can improve prognosis and patient survival.
Keywords: sarcoma; synovial; deglutition disorders